Pattern recognition applications and methods : 7th International Conference, ICPRAM 2018, Funchal, Madeira, Portugal, January 16-18, 2018, Revised selected papers /: 7th International Conference, ICPRAM 2018, Funchal, Madeira, Portugal, January 16-18, 2018, Revised selected papers. (2019) - Unknown
No abstract available